Does directly observed treatment ("DOTS") contribute to tuberculosis treatment compliance? ¿El tratamiento con supervisión directa ("DOTS") contribuye para la adhesión al tratamiento de la tuberculosis? O tratamento diretamente supervisionado (DOTS) contribui para a adesão ao tratamento da tuberculose? - Maria Fernanda Terra; Maria Rita Bertolozzi (Revista Latino-Americana de Enfermagem, 2008)
This is a qualitative study performed in the theoretical framework of the Theory of Social Determination of the Health-Disease process and the concept of Compliance. The goal was to analyze meanings of DOTS in compliance with tuberculosis treatment, according to healthcare professionals of the Technical Healthcare Supervision of Butantã (SUVIS), a region of the São Paulo City Healthcare Secretariat, Brazil. The project was submitted to the Ethics Committee of the São Paulo Municipal Health Secretariat. All professionals (22 people) developing DOTS were interviewed, including service coordinators, healthcare professionals and the DOTS coordinator for the region. The statements were analyzed with an appropriate technique for discourse analysis. The results appoint that the strategy presents more potentialities than limits and is effective regarding compliance, since it allows the professionals to welcome and monitor the patients, considering their needs. The importance of increasing the understanding of compliance is also noted, so that it can go beyond the simple intake of medication, integrating the care for the sick person and his or her necessities by transcending those restricted to the biological dimension. Se trata de un estudio cualitativo realizado bajo el marco teórico de la Teoría de la Determinación Social del Proceso Salud Enfermedad y el concepto de Adhesión. El objetivo fue analizar los significados de la DOTS en la adhesión al tratamiento de la tuberculosis, según la visión de profesionales de la salud de la Supervisión Técnica de la salud del Butanta de la Secretaría de la salud del Municipio de San Pablo. El proyecto fue sometido al Comité de Ética. Se entrevistaron la totalidad de los profesionales (22 personas) que desarrollaban la DOTS incluyendo coordinadores de servicios, profesionales asistenciales y el coordinador de la DOTS en la región. Se analizaron las declaraciones según la técnica de análisis de discurso apropiada. Los resultados apuntan que la estrategia presenta más potencialidad que límites y es efectiva en la adhesión, por permitir acoger y monitorear el enfermo considerando sus necesidades. Se apunta la importancia de ampliar el entendimiento de la adhesión, más allá de la ingestión de la medicación, integrando el cuidado del enfermo a partir de sus necesidades, trascendiendo aquellas restrictas a la dimensión biológica. Estudo qualitativo, realizado sob o marco teórico da Teoria da Determinação Social do Processo Saúde Doença e conceito Adesão. O objetivo foi analisar significados da DOTS na adesão ao tratamento da tuberculose, segundo profissionais de saúde da Supervisão Técnica de Saúde do Butantã da Secretaria de Saúde do Município de São Paulo. O projeto foi submetido ao Comitê de Ética. Entrevistou-se a totalidade dos profissionais (22 pessoas) que desenvolviam DOTS, incluindo coordenadores de serviços, profissionais assistenciais e coordenador da DOTS na região. Analisou-se os depoimentos, segundo a técnica de análise de discurso apropriada. Os resultados apontam que a estratégia apresenta mais potencialidades do que limites e efetividade na adesão, por permitir acolher e monitorar o doente considerando suas necessidades. Aponta-se a importância da ampliação do entendimento da adesão para além da ingesta da medicação, integrando o cuidado do doente a partir de suas necessidades, transcendendo aquelas restritas à dimensão biológica.